(untitled) (Research, Society and Development, 2022)
Keeping animals in zoos is important for the preservation of endangered species. However, captive animals can also be affected by different species of parasites. Herein, we aimed to evaluate the occurrence of gastrointestinal parasites in wild and exotic animals from two zoos in the state of Sergipe, Northeastern Brazil. Fecal samples were obtained by spontaneous defecation of 287 specimens, grouped into mammals (n = 101), birds (n = 99), and reptiles (n = 87). The samples were assessed using two techniques, Mini-FLOTAC and Ziehl-Neelsen, to identify helminths and protozoa, respectively. In total, 60.2% (173/287) of the animals evaluated were positive for some type of gastrointestinal parasite. Among the classes evaluated, mammals (81.1%; 82/101; p-value <0.0001) were mostly affected, followed by birds (56.6%; 56/99) and reptiles (40.2%; 35/87). Furthermore, our findings showed that the parasites Ancylostomatidae and coccidian oocysts were the most abundant among the species. It is important to highlight the first record of some parasites in species in the South America, such as: Ancylostomatidae in Asian Elephant (Elephas maximus) and Brown Bear (Ursus arctos); Toxascaris leonina in Leo (Panthera leo); and Trichostrongyloidea and Ascarididae in Equus quagga burchellii and Lama glama. Taken together, our data showed a high occurrence of gastrointestinal parasites in captive animals, including zoonotic species, which may pose a risk to animal and human public health.